Guidelines for the Development of the Potential Tourism Model, Baan Sa Kla Village Samut Prakarn Province - Rongthong, Natthakan; Thosuwonchinda, Vongvipha (Dusit Thani College Journal, 2020)
This research aims to explore tourism resources and evaluate tourism potential of Baan Sa Kla Village, Samut Prakarn Province; to propose the development model of tourism. This research is a qualitative research by using purposive sampling from stakeholders who are representative from government agencies, village representatives and tourists. Semi-structured interview was methods of collecting qualitative data in this research. A survey of the tourism resources of the Baan Sa Kla community, based on the Five A’s of Tourism criteria. It was found that the community tourism resources in full the whole composition 5 criteria, including 1) Attractions 2) Accessibilities 3) Accommodation 4) facilities and Amenities and 5) Activities. Evaluation of potential tourist attractions. Evaluation of potential tourist attractions. There were found that Baan Sa Kla community has the potential to develop into a tourist attraction in all 6 parts. The researchers designed activity as an itinerary for One Day Trip. This is a cooperation with related government agencies and local people in the community. The development of tourism in the community as a guideline for sustainable tourism management.